Restorative Justice Bagi Anak Pelaku Tindak Pidana Pembunuhan dalam Perspektif Pidana Islam - Hasuri Hasuri (Ajudikasi : Jurnal Ilmu Hukum, 2018)
The settlement of criminal cases by using the punishment method for the perpetrators (retributive) is not effective enaough and it is not become deterrent for the perpetrators but they more expert in doing criminal acts, moreover the perpetrators are children under the age that they are unstable in psychiatric and very easy to imitate the negative behavior gained in jail. Many methods of punishment offered by experts to change conventional punishment methods one of them is using the Restorative Justice, the  concept of punishment is by involving the victim's family efforts not only focus on giving suffering to the perpetrator but also healing the injuries suffered by the victim and the victim's family. This study focuses on the concept of Restorative Justice for children involved in criminal acts of murder in Islamic criminal studies, and find the differences in the application of Restorative Justice in the provision of a positive legal system in Indonesia with Islamic criminal law.